Emergency cricothyrotomy during the COVID-19 pandemic: how to suppress aerosolization. Issue 1 (6th August 2020) - Issa, Nabil; Liddy, Whitney E; Samant, Sandeep; Conley, David B; Kern, Robert C; Hungness, Eric S; Barsuk, Jeffrey H
Abstract : Background: Cricothyrotomy is associated with significant aerosolization that increases the potential risk of infection among healthcare providers. It is important to identify simple yet effective methods to suppress aerosolization and improve the safety of healthcare providers. Methods: 5 ear, nose and throat and general surgeons used a locally developed hybrid cricothyrotomy simulator with a porcine trachea to test three draping methods to suppress aerosolization during the procedure: an X-ray cassette drape, dry operating room (OR) towels and wet OR towels. The three methods were judged based on three categories: effectiveness of suppression, availability in all healthcare systems and ease of handling. Results: All five surgeons performed the procedure independently using each of the three suppression methods. The wet OR towel drape was found to be an effective method to suppress aerosolization, and it did not hinder the surgeons from performing the procedure accurately. This finding was confirmed by using an atomized fluorescein dye injection into the porcine trachea, representing aerosolized material while performing the procedure. Conclusions: We present a novel intervention using wet towels to suppress aerosolization during cricothyrotomy. Wet towels are cheap and readily available within any healthcare setting regardless of the financial resources available.